The history of the Library of the Chamber of Deputies amidst legislative body, research institutions, and librarians devoted to reference services to Members of Parliament and information assistance to external users - Guerrini, Mauro; De Laurentiis, Rossano (Bibliothecae.it, 2020)
The article analyzes the history of the Camera dei Deputati’s Library through the publication: Fernando Venturini, Libri, lettori e bibliotecari a Montecitorio. Storia della Biblioteca della Camera dei deputati, Milano, Wolters Kluwer, Padova, CEDAM, 2019 (Quaderni di Nomos. Le attualità nel diritto. Nuova serie, 7).